Development and psychometric evaluation of a quality of life questionnaire for infertile women: a mixed method study - Zahra Kiani; Masoumeh Simbar; Sepideh Hajian; Farid Zayeri (BMC, 2020)
Abstract Background Infertility is one of the most important issues that negatively influences women's quality of life, especially when the cause is associated with females. Given that no instruments have been designed to assess quality of life among infertile women with focus on female factors, this study was conducted to develop and evaluate the psychometric properties of a female-centric quality of life questionnaire for infertile women. Method This sequential exploratory study was conducted in two stages. First, the concept of quality of life and its dimensions as they relate to infertile women were elucidated through a qualitative inquiry accompanied with a content analysis. Accordingly, infertile women and key informants from a teaching hospital affiliated with the Mazandaran University of Medical Sciences and a private center for infertility treatment in Sari (north of Iran) were screened through purposive sampling until data saturation. Those who satisfied the inclusion criteria and exhibited maximum variance in terms of age, educational level, employment status, infertility duration, treatment type, and social class were recruited. The conventional content analysis was carried out in accordance with the steps proposed by Graneheim and Lundman, and the accuracy and robustness of the data were verified using Lincoln and Guba's criteria (credibility, transferability, dependability, confirmability and authenticity). Second, the psychometric properties of the instrument developed in the qualitative stage were evaluated using a quantitative method and on the basis of the results of a literature review. The content, face, and construct validity of the instrument was determined, and its test-retest reliability and stability were ascertained using internal correlation and Cronbach's alpha. The collected data were entered into the Statistical Package for the Social Sciences (version 22) for analysis, and descriptive statistics were calculated. Discussion Developing and evaluating the psychometric properties of a valid and reliable female factor-centric instrument that measures quality of life among infertile women will be very useful in the assessment of their future status.